2014
DOI: 10.1149/2.026404jss
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Current-Voltage Characteristics of Al-Doped MgxZn1-xO/AlGaNn-pJunction Diodes

Abstract: This study investigated the temperature dependence of the current-voltage (I-V) characteristics of Al-doped MgxZn1-xO/p-AlGaN junction diodes. The n-type Al-doped MgxZn1-xO (AMZO) films were deposited on p-AlGaN using a radio-frequency (rf) magnetron sputtering system followed by annealing at 700, 800, and 900°C in a nitrogen ambient for 60 s. The n-AMZO/p-AlGaN diode at a substrate temperature of 25°C showed the lowest leakage current in reverse bias. The n-AMZO/p-AlGaN diode with an AMZO annealed at 900°C de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…(3)) and dV/d(lnI)-I (Eq. (4)) plots in the forward bias, could be related to the presence of series resistance, interface states, and the voltage drop across the interfacial layer [24,25]. There is also a clear trend of decreasing the series resistances R s with the increased indium content and a rise in the testing temperature.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…(3)) and dV/d(lnI)-I (Eq. (4)) plots in the forward bias, could be related to the presence of series resistance, interface states, and the voltage drop across the interfacial layer [24,25]. There is also a clear trend of decreasing the series resistances R s with the increased indium content and a rise in the testing temperature.…”
Section: Discussionmentioning
confidence: 95%
“…The current density was 0.38 A·cm − 2 at 8 V and the breakdown voltage was~20 V [2]. Hsueh et al investigated the temperature dependence of the current-voltage characteristics of n-Mg x Zn 1 − x O/p-GaN hetero-junction diodes, the extracted ideality factors were in the range of 3.86-7.00, decreasing with an increase in the testing temperature (25-125°C) [25]. Keskenler et al studied the Ag/n-ZnO/p-Si/Al hetero-junction diode.…”
Section: Discussionmentioning
confidence: 99%
“…In the other paper, they also investigated the I-V characteristics at different testing temperatures for Al-doped Mg x Zn 1-x O/AlGaN junction diodes with Mg-ZnO made by RF sputtering on the MOCVD-grown AlGaN. The extracted ideality factors were found in the range of 5.04 -15.90, decreasing as the testing temperature increased from 25˚C to 125˚C [22]. Mohd Yusoff et al described the growth and characterization of p-n junction diode based on GaN grown on Si (111) [10].…”
Section: Discussionmentioning
confidence: 99%
“…(4)) plots in the forward bias. This difference could be related to the presence of series resistance, interface states, and the voltage drop across the interfacial layer [22,23]. A good diode is expected not to be temperature dependent in ideality factor.…”
Section: Discussionmentioning
confidence: 99%
“…After I-V measurement at RT, they reported that the barrier height and ideality factor were 0.63 70.02 eV and 4.0 70.3, respectively [5]. Hsueh et al investigated the temperature dependence of the currentvoltage characteristics of n-Mg x Zn 1À x O/p-GaN hetero-junction diodes, the extracted ideality factors n were in the range of 3.86-7.00, decreasing with an increase in the testing temperature (25-125 1C) [22]. They also investigated the I-V characteristics at different testing temperatures for Al-doped Mg x Zn 1À x O/AlGaN junction diodes with n-Mg-ZnO made by RF sputtering on the MOCVD-grown p-AlGaN.…”
Section: Discussionmentioning
confidence: 99%